Age-related resistance to Fusarium oxysporum f. sp. cepae and associated enzymatic changes in seedlings of Allium cepa and A. fistulosum - Galeano,Pablo (2014)
This research analysed the response of onion (Allium cepa) and A. fistulosum against Fusarium oxysporum f. sp. cepae (Foc) isolates and the associated changes in peroxidase, β-1,3-glucanase and chitinase activities. The response of A. cepa and A. fistulosum at different stages of seedling development were also evaluated. Several seedling tests were performed, and disease symptoms were evaluated 12-14 days after inoculation. Allium fistulosum behaved as more resistant than A. cepa cultivars by exposition to the most aggressive Foc isolates at sowing date. Increased levels of peroxidase and glucanase activities were found in the A. cepa and A. fistulosum seedlings exposed to the pathogen, and were positively correlated with disease symptoms. For chitinase activity, this correlation was found only for A. cepa. Two peroxidase isoforms were found to be specific for A. fistulosum roots after inoculation and could be involved in resistance. The inoculation at 7, 14 and 42 days after sowing showed that both host species were resistant to Foc, proving that onion susceptibility decreased promptly after germination . However, an increase in peroxidase and glucanase activities in 7-and 14-day-old inoculated seedling was detected only for A. cepa, suggesting an earlier acquisition of resistance in A. fistulosum.